2019
DOI: 10.5005/jp-journals-10077-3024
|View full text |Cite
|
Sign up to set email alerts
|

Silver Diamine Fluoride in Pediatric Dentistry

Abstract: Dental caries remains a severe oral health problem in children and its impact in terms of pain, impairment of function, and oral health-related quality of life of the population is high, especially the disadvantaged individuals and communities. Despite the widespread use of fluoride dentifrice, preschool children, compared to the other age groups, still show a high number of untreated caries lesions. Minimal and noninvasive approaches for the management of dental caries are preferred currently, in lieu of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Paiva and co-workers (2018) concluded that a higher concentration of silver (0.5% by mass) in the matrix of nano-Ag-GIC allowed viable net setting time and increased the compressive strength of the experimental cement by 32%. The addition of AgNPs increased the mechanical properties of the GIC and improved the antibacterial property in arresting the caries ( Padovani et al, 2015 ; Raggio et al, 2016 ; Paiva et al, 2018 ; Nuvvula and Mallineni, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Paiva and co-workers (2018) concluded that a higher concentration of silver (0.5% by mass) in the matrix of nano-Ag-GIC allowed viable net setting time and increased the compressive strength of the experimental cement by 32%. The addition of AgNPs increased the mechanical properties of the GIC and improved the antibacterial property in arresting the caries ( Padovani et al, 2015 ; Raggio et al, 2016 ; Paiva et al, 2018 ; Nuvvula and Mallineni, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…(18,19,20) . A protective coating of vaseline was used to avoid the possible transitory hennaappearing tattoo that may occur if SDF contacted tissues (23,24) . Pain existence in this study was due to failure of caries arrest of the lesion, extension of decay leading to abscess leading to tooth failure, it may be attributed to that some children missed their follow up and their re-application, others did have not followed oral hygiene measures properly.…”
Section: Discussionmentioning
confidence: 99%
“…Data were collected, tabulated, statistical analysis performed using Statistical Package for Social Science (SPSS)® Ver. 24 All demographic of patients in both groups were compared and revealed insignificant difference as presented in table (1).…”
Section: Figure (1): Consort Flow Diagram Showing Patient Flow During the Trialmentioning
confidence: 99%
“…Cantilever bridges and resin-bonded fixed partial denture (FPD) that are loosened or dislodged can be managed after the pandemic period if the patient is asymptomatic. The hypersensitivity of exposed abutment tooth can be governed by the self-application of silver diamine fluoride (SDF) or casein phosphopeptide amorphous calcium phosphate (CPP-ACP) to the exposed vital abutment tooth (23). Conventional fixed bridge designs that have dislodged on one abutment or one retainer are challenging to diagnose.…”
Section: Fixed Partial Denturementioning
confidence: 99%